Modal Verbs in Tyneside English - McDonald, Christine; Beal, Joan C. (Linguistica Atlantica, 1987)
Until very recently, the syntax of Tyneside English, like that of most English dialects, has been more or less neglected. This has partly been due to the methodological problems involved in collecting sufficient tokens of forms that will occur rarely in even a long stretch of speech, as is pointed out by Jones-Sargeant (1985). This paper constitutes a condensed account of a larger study carried out by the first-named author: at present, this is the only major study of Tyneside syntax to have been undertaken. The modal syntax of Tyneside differs from that of Standard English in several important ways. Firstly, may and shall are hardly used at all in Tyneside, and at best are stylistic variants of can and will respectively, there being no context in which either may or shall is compulsory. Can and could have even more ’non-modal’ characteristics in Tyneside than in Standard English. Other differences between Tyneside and Standard English include the more frequent use of ’epistemic’ must and the rarity of ought, which coincides with infrequent use of should in ’non-root, non epistemic’ uses as would be predicted by Leech & Coates (1977a and 1977b). Finally, the system of tags is totally different in Tyneside and Standard English respectively, the former having a larger set of options in which single and double negatives, contracted and uncontracted, are contrasted in order to distinguish between tags which ask for information and those requiring confirmation.